Cover Feature: Putting the Disulfide Bridge at Risk: How UV‐C Radiation Leads to Ultrafast Rupture of the S‐S Bond (ChemPhysChem 21/2018). Issue 21 (11th October 2018) - Larsen, Martin A. B.; Skov, Anders B.; Clausen, Christian M.; Ruddock, Jennifer; Stankus, Brian; Weber, Peter M.; Sølling, Theis I.
Abstract : The Cover Feature illustrates how 200 nm UV light from the sun is able to cleave disulfide bonds in peptides and damage the spatial structure, whereas this is not the case upon excitation to S1 . More information can be found in the Communication by M. A. B. Larsen et al. onpage 2829 in Issue 21, 2018 (DOI:10.1002/cphc.201800610 ).